Characterization and significance of localized sources identified by a novel automated algorithm during mapping of human persistent atrial fibrillation. (8th October 2018) - Verma, Atul; Sarkozy, Andrea; Skanes, Allan; Duytschaever, Mattias; Bulava, Alan; Urman, Roy; Amos, Yariv A.; Potter, Tom de
Abstract: Background: Automated algorithms may identify focal (FA) and rotational (RoA) activations during persistent atrial fibrillation (PeAF). Objective: To evaluate an automated algorithm for characterizing and assessing significance of FA/RoA. Methods: Eighty‐six PeAF ablation patients (1411 maps) were analyzed. Maps were obtained with a 64‐electrode basket using CARTOFINDER, which filters/annotates atrial unipolar electrograms over 30 seconds. Operators ablated FA/RoA followed by pulmonary vein isolation (PVI). The automated algorithm was retrospectively applied using QS patterns to identify FA and sequential activation gradients for RoA without phase mapping. Algorithm‐identified FA and RoA were validated against blinded adjudicators. Ablation of algorithm‐identified FA/RoA was related to procedural AF termination. Results: 73% ± 18% of electrodes (65% ± 11% atrial surface area) were adequate for analysis. Compared with adjudicators, the algorithm had a sensitivity of 84% for FA and 86% for RoA. There were 4 ± 2 FA and 2 ± 2 RoA per patient. FA occurred 8 ± 6 times during the 30‐second window (cumulative duration 8 ± 6 seconds). RoA occurred 5 ± 3 times (median 2, consecutive rotations) with a cumulative duration of 3 ± 2 seconds. Compared to patients without procedural AF termination, patients with termination had more FA ablated (75% vs 38%, P  = 0.006). AF termination was not predicted by percentage of RoA ablated although there was a trend towards a higher percentage of left atrial RoA ablated ( P  = 0.06). Conclusion: An automated algorithm had high sensitivity for FA and RoA. Acute AF termination was associated with FA ablation but not RoA ablation. Future studies need to define the significance of FA and RoA and whether they are overlapping or separate mechanisms.